La cuestión de la ideología de género y sus implicaciones teológica (2018)
This article aims to show what the implications of gender ideology are and how it affects the social dimension of the human being. To that extent, an approach will be made from a philosophical-theological perspective, which seeks to account for the genesis of this ideology, its evolution, its fundaments and its practical consequences